A high dust emissivity index β for a CO-faint galaxy in a filamentary Lyα nebula at z = 3.1. (6th September 2018) - Kato, Yuta; Matsuda, Yuichi; Iono, Daisuke; Hatsukade, Bunyo; Umehata, Hideki; Kohno, Kotaro; Alexander, David M; Ao, Yiping; Chapman, Scott C; Hayes, Matthew; Kubo, Mariko; Lehmer, Bret D; et al.
Abstract: We present CO J = 4–3 line and 3 mm dust continuum observations of a 100 kpc-scale filamentary Lyα nebula (SSA22 LAB18) at z = 3.1 using the Atacama Large Millimeter/submillimeter Array (ALMA). We detected the CO J = 4–3 line at a systemic z CO = 3.093 ± 0.001 at 11 σ from one of the ALMA continuum sources associated with the Lyα filament. We estimated the CO J = 4–3 luminosity of $L^{′ }_{\rm {CO(4-3)}}=(2.3 ± 0.2)× 10^{9}\:$ K km s −1 pc 2 for this CO source, which is one order of magnitude smaller than those of typical z > 1 dusty star-forming galaxies (DSFGs) of similar far-infrared luminosity L IR ∼ 10 12 L ⊙ . We derived a molecular gas mass of $M_{\rm {gas}} = (4.4^{+0.9}_{-0.6}) × 10^{9}\, M_{{\odot }}$ and a star-formation rate of SFR =270 ± 160 M ⊙ yr −1 . We also estimated a gas depletion time of τdep = 17 ± 10 Myr, which is shorter than those of typical DSFGs. It is suggested that this source is in the transition phase from DSFG to a gas-poor, early-type galaxy. From ALMA to Herschel multi-band dust continuum observations, we measured a dust emissivity index β = 2.3 ± 0.2, which is similar to those of local gas-poor, early-type galaxies. From recent laboratory experiments, the specific chemical compositions needed to reproduce such a high β for interstellar dust at the submillimeter wavelengths. ALMA CO and multi-band dust continuum observations can constrain the evolutionary stage of high-redshift galaxies through τdep and β, and thus we can investigate the chemical composition of dust even in the early Universe.